Local ecological knowledge dynamics of farmers in areas which have been chronically disturbed by human actions in the Brazilian Caatinga - Marques, Kamila; Ramos, Maiara Bezerra; Silva da Cunha, Sonaly; Rodrigues Maciel, Maria Gracielle; de Souza, Stefanny Martins; La Torre-Cuadros, María de los Ángeles; Lopes, Sérgio de Faria (Ethnobotany Research and Applications, 2022)
Background: The diversity of plants indicated for the same use, plays important strategies which can affect the resilience of local ecological knowledge. In this context, we investigated the variation of local ecological knowledge through the richness of cited species, redundancy on an individual level and utilitarian redundancy (fuel, construction and technology) by local populations inserted in a dry forest with different environmental characteristics in northeastern Brazil. Methods: We conducted semi-structured interviews with 120 local experts and described metrics which indicate the intensity of chronic human disturbance, defined as ongoing activities to remove natural resources, as well as the average annual rainfall in forests close to populations. Results: We verified that there are differences between the number of species mentioned and the utilitarian redundancy between the studied areas. The richness of known species is suggested to influence redundancy on an individual level. Furthermore, we observed that information sharing about the plants among local experts is different, as some species were shared more than others. Conclusions: Our results suggest that people living in areas of greater chronic anthropic impact and less rainfall may be subject to a lower resilience of local knowledge. Keywords: Caatinga; ethnobotany; redundancy; chronic anthropic disorders.